Microencapsulated Recombinant Human Epidermal Growth Factor Ameliorates Osteoarthritis in a Murine Model. (23rd September 2021) - Lin, Shih-Chao; Zhang, Xiang; Chen, Shiow-Yi; Lin, Chi-Chien; Chiu, Yen-Shuo
Abstract : Osteoarthritis, a highly age-related and chronic inflammatory disorder with cartilage loss, causes patients difficultly in movement; there is no efficient and sustainable remedy for osteoarthritis currently. Although hyaluronic acid (HA) and platelet-rich plasma (PRP) have been used to alleviate osteoarthritis, the effects could be short and multiple injections might be required. To address this issue, we exploited the property of chitosan to encapsulate recombinant human epidermal growth factor and obtained microencapsulated rhEGF (Me-rhEGF). In the current study, we induced the osteoarthritis-like symptoms with monosodium iodoacetate (MIA) in rats and investigated the therapeutic effects of Me-rhEGF. Following administration of HA/Me-rhEGF in vivo, we observed that the total Mankin scores, cartilage oligomeric protein, C-telopeptide of type II collagen, IL-1 β, IL-6, IL-17A, and TNF- α cytokines, nitric oxide, and prostaglandin E2 expressions were significantly inhibited. Our results also strongly indicate that individual use of HA or rhEGF slightly decreased the inflammation and restored the destructive joint structure, but was not as drastic as seen in the HA/Me-rhEGF. Moreover, HA/Me-rhEGF profoundly reduced cartilage destruction and proteoglycan loss and downregulated matrix metalloproteinase expressions. These findings reveal that the treatment of HA/Me-rhEGF could be more beneficial than the use of single HA or rhEGF in reliving osteoarthritis and demonstrate the therapeutic application of microencapsulation technology in difficult joint disorders. In essence, we believe that the Me-rhEGF could be promising for further research and development as a clinical treatment against osteoarthritis.